Weryfikacja skuteczności parametrycznych oraz nieparametrycznych modeli prognozowania upadłości przedsiębiorstw - Korol, Tomasz (Verification of Effectiveness of Parametric and Nonparametric Bankruptcy Prediction Models, 2008)
This article is on bankruptcy prediction of the stock equity companies with the use of different pa-rametric and nonparametric techniques. The author created 8 models for analyzing the companies one year and two years prior to their financial failure. Models presented in the article allow to predict with a high probability bankruptcy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 314-321